Theory and Practice of Quality and Reliability Engineering in Asia Industry - Tan, Cher Ming.; Goh, Thong Ngee.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book discusses the application of quality and reliability engineering in Asian industries, and offers information for multinational companies (MNC) looking to transfer some of their operation and manufacturing capabilities to Asia and at the same time maintain high levels of reliability and quality. It is also provides small and medium enterprises (SME) in Asia with insights into producing high-quality and reliable products. It mainly comprises peer-reviewed papers that were presented at the Asian Network for Quality (ANQ) Congress 2014 held in Singapore (August, 2014), which provides a platform for companies, especially those within Asia where rapid changes and growth in manufacturing are taking place, to present their quality and reliability practices. The book presents practical demonstrations of how quality and reliability methodologies can be modified for the unique Asian market, and as such is a valuable resource for students, academics, professionals and practitioners inthe field of quality and reliability.
Quality Engineering Today -- Overview of Reliability Engineering -- Identifying the Source of Variance Shifts in Multivibrate Statistical Process Control Using Ensemble Classifiers -- Nonparametric Wavelet-based Multivariate Control Chart for Rotating Machinery Condition Monitoring -- From Belts to Baldrige -- Risk Management in Internal Audit Planning -- Analysis of Students' Feedback to Improve Course Programme -- The Impact of ASEAN University Network-Quality Assurance (AUN-QA) Assessment on the Quality of Educational Programmes -- The Evaluation of Service Quality for High Education in Taiwan by Using Importance-Satisfaction Model. .
Keywords: Security systems; Production management; Industrial Management; Security Science and Technology; Operations Management; Industrial Management